Features of Hyaluronic Acid Solutions for Intra-articular Introduction and Recent Trends in Their Development (Review) - Y. Y. Zagorulko; E. Y. Zagorulko (Разработка и регистрация лекарственных средств, 2020)
Introduction. The most common way to maintain the viscoelastic properties of synovial fluid is intra-articular administration of hyaluronic acid solutions. Such forms have several features due to the method of administration, the characteristics of the substance, as well as their composition, technology, and packaging. The aim of the work to analyze the features of hyaluronic acid solutions for intra-articular administration, as well as to consider resent trends to their pharmaceutical development.Text. Currently, in Russia, most of these forms are registered as medical devices. Each drug has its characteristics, including the source of the substance, the main molecular weight and the molecular weight range of hyaluronic acid, the structure of the molecule (linear or cross-linked), the method of its chemical modification, concentration, solution volume, dosage, etc. As excipients most often use sodium chloride, water for injection, and phosphate-buffered saline to maintain pH values close to the synovial fluid. Some prostheses contain mannitol as an antioxidant. Combinations of hyaluronic acid with active chondroprotective substances (chondroitin sulfate, sodium succinate) are known. The main type of primary packaging is glass prefilled syringes. The choice of sterilization methods is determined by the chemical structure of hyaluronic acid, aseptic production is used for most prostheses.Conclusion. Currently, research solutions to create thermostable and enzyme-resistant compositions with hyaluronic acid for intra-articular administration are being successfully applied. Modern developments are aimed at creating polymer complexes of hyaluronic acid with substances that improve the lubricity of solutions, the development of nanosystems (liposomes, nanoparticles, nano micelles, etc.) with chondroprotective, as well as the creation of inert biocompatible prostheses with viscoelastic properties. The creation of forms of hyaluronic acid and alternative drugs that can support the rheological properties of synovial fluid is currently a promising area of research.